Protocol Division Roles in Facilitating Regional Head Activities: A Public Management Study at a Regional Secretariat - Martina Jovyta Adonia Sampul; Evi E. Masengi; Steven V. Tarore (JR Education, 2026)
This article analyzes the role of the Protocol and Leadership Communication Division in facilitating the official activities of a regional head within a city regional secretariat. Although protocol work is often perceived as ceremonial, the findings show that it operates as a strategic public management function involving coordination, agenda governance, event arrangement, and field assistance for the regional head. Using a qualitative descriptive approach, data were obtained from interviews, observation, and documentation and were analyzed through the interactive model of data condensation, data display, and conclusion drawing. The study found that the protocol division contributed substantially to the smoothness of regional-head activities through structured cross-agency coordination, rapid formal and informal communication, systematic agenda management, technical event preparation, and direct leadership assistance in the field. However, implementation was constrained by delayed information from organizing agencies, sudden schedule changes, incomplete technical data, limited protocol personnel when activities occurred simultaneously, and different perceptions among agencies regarding protocol standards. The article argues that the protocol function should be understood not only as ceremonial support but also as an integrative administrative mechanism that connects leadership mobility, organizational coordination, public symbolism, and service quality. The recommended improvement strategy includes strengthening integrated digital agenda management, standardizing cross-agency operating procedures, improving early notification discipline, building protocol contingency capacity, and institutionalizing documentation-based coordination. The article contributes to public administration by demonstrating how protocol management supports administrative effectiveness, leadership legitimacy, and the operational quality of local government activities.